The Effect of Infusion of Syzygium polyanthum (Wight) Walp. Leaves as Natural Preservative Chicken Meats - Hartanti, Dwi; Djalil, Asmiyenti Djaliasrin; Hamad, Alwani; Yulianingsih, Nur (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2019)
Syzygium polyanthum (Wight) Walp. (Indonesian bay leaf) is known for possessing antimicrobial activity that might be applied for natural food preservative. In this study, we analyzed the constituents of infusion of S. polyanthum leaves and evaluated its potency as the preservative of fresh chicken meats. The infusions were prepared with the method described in Indonesian Pharmacopeia. Phytochemical content of infusion of S. polyanthum leaves was analyzed by qualitative phytochemical screening using colorimetric methods. Its application for preservative of fresh chicken meat was evaluated based on its activity in inhibiting the growth of bacteria on the meats as well as the physical observation of the preserved meats. The infusion of S. polyanthum leaves contained flavonoids, tannins, and saponins. The infusion at the optimum concentration of 10% was capable of inhibiting bacterial growth on chicken meats and extending their shelf life up to 3 days in temperature of 3-7ºC.